Effect of double layer stent to flow phenomena in cerebral aneurysm - Muhammad Aizat Zuhair, Mohd Azly (2009)
The investigation is about the flow pattern in blood vessel that has been done at the aneurysm with the different type of stent. The velocity profile and the pressure distribution of blood had been identified from the stent implantation. There are three types of stent model in this case study which known as Type 1, Type 2 and Types 3. All types of stent that has been applied to the aneurysm are in double layer. A non-stented and stented aneurysm need be considered for identifying the changes in hemodynamics due to stent implantation. The simulation of the model was studied under incompressible, non-Newtonian, viscous, non-pulsatile condition in which we investigated computationally in a three-dimensional configuration using a fluid dynamics program. The different structure of stent has given the different flow pattern around the aneurysm region. The minimum velocity has been increased after the stent implantation and stent Type 3 has given the optimum result with the low pressure and the highest minimum velocity. Finally, the correlations obtained from this numerical result could be used to investigate the pressure distribution around the diseased segment.